Application of Boost Inverter For Grid Connected Fuel Cell Based Power Generation - Ms. Manminder Kaur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The boost inverter architecture is used as a building block in this research to create a single phase grid connected fuel cell (FC) system with low cost and compactness. In addition, to support the FC's sluggish dynamics, the proposed system includes battery-based energy storage and a dc-dc bidirectional converter. The voltage mode of the single phase boost converter is maintained, but the low frequency current ripple is regulated by the current mode. The battery provides the low frequency current ripple, which mitigates the impacts of such ripple pulled straight from the FC. This technology, however, may work in either a grid-connected or independent mode. In grid linked mode, the boost inverter can regulate the active (P) and reactive (Q) powers using a second order generalised integrator algorithm that offers rapid signal conditioning for single phase circuits. At the grid side, we may lower Total Harmonic Distortion (THD). In addition, we have a backup storage device to accommodate the sluggish dynamics of the FC sources that are all integrated into one system. To confirm the performance of the proposed system, a design model and guidelines, simulation, and experimental findings from a laboratory prototype are available